2011
DOI: 10.4103/0972-0707.87203
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective clinical evaluation of success rate in endodontic-treated premolars restored with composite resin and fiber reinforced composite posts

Abstract: Background:The aim of this retrospective study was to assess the survival rate and causes of failure of quartz fiber posts used to restore endodontically treated teeth.Materials and Methods:Thirty-eight patients with endodontically treated premolar and anterior teeth that were then restored with a coronoradicular quartz fiber post and extensive composite resin restorations were selected for participation in the study. The age of the restorations ranged from 1 to 6 years. Survival probabilities of the restorati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 19 publications
1
8
0
1
Order By: Relevance
“…The latter finding was also confirmed in the present study: among the 12 failures in the maxillary arch, more failures occurred in the posterior than the anterior teeth, at a ratio of 2 to 1 ( Table 2). In a previous retrospective study, 30 the dental arch was found to be a significant predictive factor of failure, with teeth in the maxillary arch having a higher failure rate than teeth in the mandibular arch, as in the present study. Conflicting observations have been reported, with some studies showing a greater percentage of failures in the anterior sector than the posterior, 23,31 while others have reported the opposite.…”
Section: Discussionsupporting
confidence: 45%
See 1 more Smart Citation
“…The latter finding was also confirmed in the present study: among the 12 failures in the maxillary arch, more failures occurred in the posterior than the anterior teeth, at a ratio of 2 to 1 ( Table 2). In a previous retrospective study, 30 the dental arch was found to be a significant predictive factor of failure, with teeth in the maxillary arch having a higher failure rate than teeth in the mandibular arch, as in the present study. Conflicting observations have been reported, with some studies showing a greater percentage of failures in the anterior sector than the posterior, 23,31 while others have reported the opposite.…”
Section: Discussionsupporting
confidence: 45%
“…26,27 Despite the increasing use of clear-colored and lightconductive fiber posts, few longitudinal studies of this type of restoration have been performed, particularly over the medium and long term. [19][20][21][28][29][30] Ferrari et al 19 analyzed different types of carbon and quartz fiber posts and demonstrated a low failure rate of 3.2% at 6 years, with no failures due to root fracture. Studies on glass fiber posts reported a failure rate of 12.8% at 2 years, 20.1% at 5 years, and 32.5% at 6.5 years.…”
mentioning
confidence: 99%
“…, Ghavamnasiri et al . ). Considerable differences exist between anterior and posterior teeth in the indications for fibre posts (Naumann et al .…”
Section: The Most Important Factors In Selecting the Restorative Apprmentioning
confidence: 97%
“…3 Post debonding is one possible failure caused by the complexity of bonding to root canals. 4,5 Another commonly reported failure is fracture of the post and/or core.…”
Section: Introductionmentioning
confidence: 99%